2018
DOI: 10.12688/f1000research.17199.1
|View full text |Cite
|
Sign up to set email alerts
|

Intra-canal medication containing silver nanoparticle versus calcium hydroxide in reducing postoperative pain: A randomized clinical trial

Abstract: Background: Pain of endodontic origin can be annoying for patients and endodontist. Pain relief is more important to the patient than treatment success. Numerous factors such as over instrumentation, over filling, debris extrusion can cause postoperative pain. However, bacteria found in the root canal space is the most important factor. Therefore mechanical preparation is an important step in elimination of micro-organisms from the root canal. It has been reported that micro-organisms can still survive inside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
5
1
1
Order By: Relevance
“…Both Ca(OH) 2 or AgNPs groups showed statistically significantly lower median pain scores with no statistically significant difference between them. This came in contradiction with an earlier study that found significantly lower pain scores in the AgNPs group at 4, 12, and 24 h in comparison to Ca(OH) 2 , while at 48 h postoperatively, there was no statistically significant difference [9]. A possible explanation may be due to the presence of pre-operative pain at the start of the study mentioned above, which can affect the levels of post-operative pain [32].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Both Ca(OH) 2 or AgNPs groups showed statistically significantly lower median pain scores with no statistically significant difference between them. This came in contradiction with an earlier study that found significantly lower pain scores in the AgNPs group at 4, 12, and 24 h in comparison to Ca(OH) 2 , while at 48 h postoperatively, there was no statistically significant difference [9]. A possible explanation may be due to the presence of pre-operative pain at the start of the study mentioned above, which can affect the levels of post-operative pain [32].…”
Section: Discussioncontrasting
confidence: 80%
“…Lately, silver nanoparticles (AgNPs) have gained much attention due to their unique characteristics, which lead to being incorporated in various dental materials [7]. AgNPs seem to be potential antibacterial agents due to their large surface-to-volume ratios and surface structure which can be a valuable additive to endodontic materials [8], and specifically as an intracanal medication alone [9] or in combination with Ca(OH) 2 . This combination has shown noticeable ability to reduce the bacterial count in root canals contaminated with Enterococcus faecalis [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 24 included studies, nineteen were in vitro [ 1 , 9 , 10 , 12 , 19 – 23 , 26 29 , 31 36 ], three ex vivo [ 3 , 4 , 25 ], and two in vivo [ 24 , 30 ]. About 16 studies evaluated the antibacterial efficacy of AgNPs as an intracanal medicament [ 1 , 3 , 4 , 9 , 10 , 19 , 21 – 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study on the efficacy of AgNPs as an intracanal medicament to mitigate postoperative pain in necrotic teeth with apical periodontitis after 4, 12, and 24 h showed that they were significantly more effective than Ca(OH) 2 ; however, no significant difference was observed after 48 h [ 135 ]. Another randomized controlled clinical trial evaluated the effect of using Ca(OH) 2 /AgNPs (0.03 μg/mL concentration) in 2:1 ratio or Ca(OH) 2 individually as an intracanal medicament in reducing postoperative pain and intracanal bacterial count, and showed that Ca(OH) 2 /AgNPs decreased the count of intracanal bacteria more than each one alone, although this difference was not significant for aerobic intracanal bacteria.…”
Section: Application Of Agnps In Endodonticsmentioning
confidence: 99%